Budowa systemu informacyjnego budżetowania na przykładzie budżetu kosztów transportu - Kes, Zdzisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article describes issues related to the structure of budgeting system. Budgeting has been shown as a package of controlling procedures whose complexity depends on specificity of enterprise, the kind and size of activities, organizational culture and purposes of budgeting. The paper presents periods of creating information budgeting systems on the example of cost transportation planning. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 49-57